DARK CHOCOLATE’S EFFECT ON MENSTRUAL PAIN IN LATE ADOLESCENTS - Sandy Isna Maharani; Noor Pramono; Sri Wahyuni (Belitung Raya Foundation, Indonesia, 2017)
Background: Menstrual pain can be severe enough to interfere with everyday activities for a few days every month, particularly in activities in homes and schools for late adolescents. Dark chocolate is considered effective in reducing menstrual pain. However, little is known about its effect. Objective: This study aimed to examine the effect of dark chocolate on menstrual pain in late adolescents. Methods: This was a true experiment study with randomized pretest-posttest with control group design. This study was conducted from September to November 2016 at the Bhakti Husada Boarding School of Poltekkes Kemenkes Semarang. There were 50 samples recruited by simple random sampling, with 25 randomly assigned to the experiment and control group. Numeric Rate Scale (NRS) was used to measure pain. Independent t-test and Mann-Whitney were used to examine the effect of intervention. Results: There were significant differences in menstrual pain (p <0.001) before and after treatment. The mean of menstrual pain in the treatment group (2.76 ) was lower than the menstrual pain in the control group (5.36) with p <0.001. Conclusion: Dark chocolate could reduce menstrual pain significantly in the late adolescents.